The Role of International Institutions in Law Enforcement and Human Rights in the Palestinian-Israeli Conflict - Putri, Angelina; Dinata, M. Ruhly Kesuma; Edrisy, Ibrahim Fikma (Magister Ilmu Hukum Fakultas Hukum Universitas 17 Agustus 1945 Surabaya, 2025)
The Palestine-Israel conflict is one of the longest and most complex conflicts in modern history, which has resulted in various human rights violations (HAM), such as the killing of civilians, and the destruction of vital infrastructure. This study aims to analyze the role of international institutions in enforcing law and human rights during this conflict, focusing on bodies such as the United Nations (UN), the International Court of Justice (ICJ), and the International Criminal Court (ICC). This study uses a normative legal method with a descriptive-analytical approach, reviewing related legal literature and documents to evaluate international law enforcement efforts by these institutions. The results of the study show that although international institutions play an important role in promoting peace and legal accountability, their effectiveness is hampered by political interests, especially the veto power held by permanent members of the UN Security Council, such as the United States which often supports Israel. In addition, the ICC does not have full jurisdiction over Israel because Israel is not a party to the Rome Statute, so that law enforcement against violations in the Palestinian territories is less than optimal. This study offers novelty by emphasizing the need for reform of international law enforcement mechanisms, especially limiting the use of vetoes and empowering international institutions to address violations of humanitarian law. This study makes an important contribution to the discourse on international law enforcement, by proposing reforms aimed at improving the effectiveness of international institutions in ensuring accountability and justice in conflict zones.